Функциональная верификация переходов конечных автоматов при помощи языка systemverilog - Пшеничный, К. Ю. (ХНУРЕ, 2019)
The given work is devoted to finite state machines transition path coverage using functional verification capabilities of SystemVerilog hardware description language. Cover directives method for transition path coverage has been proposed in this paper.